Formulative Study and Characterization of Novel Biomaterials Based on Chitosan/Hydrolyzed Collagen Films - Tomás Martínez Rodríguez; Caterina Valentino; Francisco Ramón Rodríguez Pozo; Pablo Hernández Benavides; Francisco Arrebola Vargas; José Manuel Paredes; Claro Ignacio Sainz-Díaz; Guillermo R. Iglesias; Silvia Rossi; Giuseppina Sandri; María del Mar Medina Pérez; Carola Aguzzi (Journal of Functional Biomaterials, 2024)
To date, the need for biomaterials capable of improving the treatment of chronic skin wounds remains a clinical challenge. The aim of the present work is to formulate and characterize chitosan (Cs)/hydrolyzed collagen (HC) films as potential biomaterials with improved mechanical and hydration performances compared to single component formulations. Films were made by the solvent casting method, with or without glycerin and/or PEG1500 as plasticizers, resulting in a total of eight formulations. All films were characterized by their physico-chemical characteristics and their mechanical and hydration features. A full factorial design was also used to statistically assess the effect of HC concentration, type and concentration of plasticizers and their possible interactions on mechanical and swelling behaviors. Solid state characterization confirmed the hybrid nature of the films, with suggested electrostatic interactions between Cs and HC. Mechanical and swelling properties, along with the analysis of the experimental design, allowed the identification of formulations containing high HC concentration (2% w/v) and glycerin or glycerin/PEG1500 as more suitable candidates for skin wound treatment. Finally, viability assay of immortalized human keratinocytes (HaCaT) showed no statistical differences in cell survival compared to the complete culture medium, suggesting their potential as a promising tool for biomedical applications.